An Analysis of the Notion of Gender and Identity: A Scholarly Exploration via Archaeological Lens (International Journal of Food and Nutritional Sciences, 2022)
The dynamics of relationships across various social groups, including families, different socioeconomic levels, age cohorts, and religious communities, can be better understood by examining the interplay between genders. Gender, as a concept, is reflected in material culture and serves as a marker that showcases the social construction of culture. In the field of archaeology, the categorization of gender goes beyond a simplistic binary division of male and female. It is crucial to recognize that gender encompasses a wide range of identities, as is evident in the present context. This recognition necessitates acknowledging the existence of diverse gender identities, such as transgender individuals, pansexual individuals, alongside conventional categories of women and men. The emergence of gender archaeology in the 1980s aimed to transform archaeological methodologies, drawing influence from various disciplines within the humanities, civil rights movements, and the broader field of anthropology. It is important to note that the representation of sex and gender may not have held significant importance throughout history, and the understanding of sex, gender, and sexuality may have been fluid and variable within different societal contexts